Epidemiological studies on the Incidence and Distribution of Leaf Spot Disease in Ashwagandha (Withania somnifera) Caused by Alternaria alternata - Sudhanshu Vats; Ram Suman Mishra; Abhishek Katiyar (The Bioscan, 2025)
Medicinal and aromatic plant Withania somnifera (Ashwagandha), is integral to Indian traditional medicine and the herbal pharmaceutical industry, owing to their rich content of bioactive compounds like alkaloids, glycosides, flavonoids. However, their commercial cultivation is severely impacted by fungal diseases, particularly foliar infections, which reduce yield, compromise quality, and alter the efficacy of pharmacologically important metabolites. Ashwagandha showed early disease symptoms in the 43rd SMW, with severity peaking at 38.77% in the 13th SMW due to rainfall and sustained humidity. In Ashwagandha, T9 achieved over 81% control for both metrics at early stages.